Disequilibrium in natural decay series in samples from Czech water treatment plants: Uranium, radium and thorium isotopes determination - Doksanská, Tereza; Kelnarová, Alena (Journal of environmental radioactivity, 2025)
In the Czech Republic, underground or mixed source water treatment plants are classified as the workplaces with possible increased exposure from a natural source of radiation. When releasing waste materials or residues from these NORM workplaces into the environment, the content of natural radionuclides is measured and compared with the clearance levels established by Czech legislation. The content of natural radionuclides in solid samples is determined primarily by high-resolution gamma-ray spectrometry. Six radionuclides, 238U, 228Th, 226Ra, 228Ra, 210Pb, 40K, are measured directly or by their measurable decay products (assuming equilibrium), the activity concentration of the other four radionuclides, 234U, 230Th, 210Po, 232Th is conservatively estimated. The study is focused on mapping the properties of NORM arising from the treatment of groundwater and, based on the real samples measurement, verification of new proposed assessment approach. It was tested whether the knowledge of the content of natural radionuclides in water can be practically used to estimate the content in NORM. Samples of water, filter material or sludge were taken from 16 different water treatment plants. Combination of gamma-ray spectrometry and radiochemical methods were applied to determine the content of radionuclides 234U, 238U, 226Ra, 228Ra, 228Th, 230Th and 232Th in solid NORM, and radionuclides 234U, 238U, 226Ra, 228Ra in water. Based on the results the proposed modification of the assessment was verified.
Keywords: Water treatment plant; Water Pollutants, Radioactive; Spectrometry, Gamma; radium; monitorování radiace; Radium; Radiation Monitoring; Thorium; čištění vody; uran; Uranium; spektrometrie gama; Water Purification; thorium; Czech Republic; NORM; Disequilibrium in decay series; Česká republika; radioaktivní látky znečišťující vodu